Promoting the Resilience of the Italian Population Against SARS-CoV-2 - Bottaccioli, Anna Giulia; Lazzari, David; Bottaccioli, Francesco (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic, due to its exceptional level of impact on the populations of the richest and most technologically advanced nations - which are experiencing unprecedented widespread mortality, fear and social isolation - due to the considerable difficulties faced by health services in coping with the emergency and the uncertainty regarding the evolution of the pandemic and its foreseeable heavy economic repercussions on a global scale, requires a change in the approach to the prevention and treatment of the infection, based on the integration of biomedical and psychological sciences and professions. A survey of the Italian pandemic population, the results of which we report here, shows a widespread state of psychological distress which, based on decades of scientific and clinical evidence on the relationship between mental states and immune system efficiency that we summarise in this paper, plausibly weakens the resistance of individuals and the population to SARS-CoV-2 infection. Italy can deploy a great force, represented by tens of thousands of psychologists and psychotherapists, who, as health workers, could be employed, alongside local and hospital medicine, in primary care and in promoting the resilience of citizens and health workers themselves, who are subject to a deadly work stress that also includes a widespread threat to their lives.